A model of educational activity methodical support and the implementation of Federal State Educational Standard of general education - Trushnikov D. Y., Dolgikh I. M. (Pedagogical excellence and pedagogical technologies, 2016)
the article provides a model of methodological support of educational activities, which is implemented in the activities of the municipal treasury office "Information and Methodological Center for the Development of Education" (IMCDE) of Purovsky district. The authors generalize the experience of IMCDE and model the possible development of institution points from the position of the current state of education system in the Russian Federation.
Keywords: инновация; ФГОС; единое методическое пространство; innovation; FSES; unified methodological space; pedagogical view; педагогическая панорама; профессиональные затруднения педагогов; professional difficulties of teachers